Modelling Frequency, Attestation, and Corpus-Based Information with OntoLex-FrAC - Chiarcos, Christian; Apostol, Elena Simona; Kabashi, Besim; Truica, Ciprian Octavian (Proceedings - International Conference on Computational Linguistics, COLING, 2022)
OntoLex-Lemon has become a de facto standard for lexical resources in the web of data. This paper provides the first overall description of the emerging OntoLex module for Frequency, Attestations, and Corpus-Based Information (OntoLex-FrAC) that is intended to complement OntoLex-Lemon with the necessary vocabulary to represent major types of information found in or automatically derived from corpora, for applications in both language technology and the language sciences.
CRIS-Team Scopus Importer:2024-12-16